The association of problematic use of social media and online videogames with aggression is mediated by insomnia severity: A cross‐sectional study in a sample of 18‐ to 24‐year‐old individuals. Issue 3 (6th December 2021) - Bersani, Francesco Saverio; Barchielli, Benedetta; Ferracuti, Stefano; Panno, Angelo; Carbone, Giuseppe A.; Massullo, Chiara; Farina, Benedetto; Corazza, Ornella; Prevete, Elisabeth; Tarsitani, Lorenzo; Pasquini, Massimo; Biondi, Massimo; et al.
Abstract: One of the worrying concomitants of problematic use of Internet (PUI) is aggression. Although the mechanisms underlying such link have not been completely clarified, it has been suggested that problematic use of social media and online videogames (i.e., two common forms of PUI among young adults) lead to increased sleep disturbances which, in turn, represent a relevant trigger for aggression. We have tested this hypothesis in a sample ( N  = 480) of young individuals (351 females and 129 males; mean age: 21.76 ± 1.92 years; range: 18–24). Self‐report measures investigating symptoms related to social media addiction (SMA), Internet gaming disorder (IGD), insomnia severity, and aggression were used. Mediational models analyzing the direct and indirect associations of SMA‐ and IGD‐related symptoms on aggression severity through insomnia‐related symptoms were performed controlling for confounding factors. The models showed that the total effects of SMA‐related symptoms ( B  = 0.018; p  = .010) and of IGD‐related symptoms ( B  = 0.018; p  = .041) on aggression severity were significant and that these associations were mediated by insomnia‐related symptoms (respectively,   p  < .001 and p  = .003). Our findings support the potential mediating role of insomnia severity in the association of SMA‐ and IGD‐related disturbances with levels of aggression.